(untitled) (Global Journal of Human-Social Science, 2020)
The main objective of this project is to investigate how active methodologies, based on workshops with environmental themes, can help high school students to learn subject matter in the area of the chemistry, physics and mathematics sciences and enhance their awareness of the importance of the preservation of the planet. In this study, 13 schools were visited in 4 years. During this time they participated in workshops that involved the use of residues to produce new materials, to provide environmental education regarding the reuse of waste and concepts embedded in the chemistry, physics and mathematics sciences. The results highlight that most of the students (98%) found the Mobile Science project interesting, 97% enjoyed participating in the workshops. Regarding the content of the workshops, 92% of the students answered positively; that is, the workshops were related and helped to understand the exact sciences. The Mobile Science project is part of the Unisul´s actions aligned to sustainable development goals (SDGs), UN 2030 Agenda.